Improving Sensitivity of a Chemoresistive Hydrogen Sensor by Combining ZIF-8 and ZIF-67 Nanocrystals - Daniel Matatagui; Arianee Sainz-Vidal; Isabel Gràcia; Eduardo Figueras; Carles Cané; José Saniger (Proceedings, 2017)
In the present work, nanostructures of zeolitic imidazolate frameworks (ZIF-8 and ZIF-67) were combined to obtain a novel chemoresistive sensor, improving the sensitivity of ZIF-67 and facilitating measurement of ZIF-8 by decreasing the resistivity. The sensor detected concentrations as low as 10 ppm of hydrogen increasing its resistivity about 4.5 times. The response of the sensor was compared with a similar chemoresistive sensor based exclusively on ZIF-67, and the sensitivity was around three times higher in the case of the sensor with ZIFs combination.